Toleransi varietas jagung (Zea mays) terhadap cekaman kekeringan pada fase perkecambahan dan vegetatif menggunakan tingkat konsentrasi PEG 6000 - Virgiana Fitri Utari (Journal of Agrosociology and Sustainability, 2023)
Corn (Zea mays L) is the second strategic commodity after rice. Limitations and uncertainties in water supply due to global warming are factors causing drought stress on agricultural land. One strategy to develop maize on dry land is to develop drought-tolerant varieties. This study aimed to determine the effect of PEG 6000 with different concentrations of four maize varieties on the drought stress tolerance of maize during the germination and vegetative phases. This research was from August to November 2020 at BPTP Banten and the Soil and Agro-climate Laboratory, Department of Agroecotechnology, Faculty of Agriculture, Sultan Ageng Tirtayasa University. This study used a Completely Randomized Factorial Design (CRD) which consisted of two factors and three replications. The first factor is the corn variety which has four levels, namely A1 (Nasa-29), A2 (JH-27), A3 (JH 45), and A4 (Lamuru). The second factor is the concentration of PEG 6000 which consists of 5 levels, namely B1 (Control), B2 (5%), B3 (10%), B4 (15%), and B5 (20%). The results showed that each concentration of PEG 6000 produced varying results. Increasing concentrations of PEG 6000 decreased yields on vigor index, germination, root length, plumula length, seedling dry weight, and drought stress sensitivity index.